Ecosystem effects of the world's largest invasive animal. Issue 5 (18th February 2020) - Shurin, Jonathan B.; Aranguren-Riaño, Nelson; Duque Negro, Daniel; Echeverri Lopez, David; Jones, Natalie T.; Laverde‐R, Oscar; Neu, Alexander; Pedroza Ramos, Adriana
Abstract: The keystone roles of mega‐fauna in many terrestrial ecosystems have been lost to defaunation. Large predators and herbivores often play keystone roles in their native ranges, and some have established invasive populations in new biogeographic regions. However, few empirical examples are available to guide expectations about how mega‐fauna affect ecosystems in novel environmental and evolutionary contexts. We examined the impacts on aquatic ecosystems of an emerging population of hippopotamus ( Hippopotamus amphibus ) that has been growing in Colombia over the last 25 yr. Hippos in Africa fertilize lakes and rivers by grazing on land and excreting wastes in the water. Stable isotopes indicate that terrestrial sources contribute more carbon in Colombian lakes containing hippo populations, and daily dissolved oxygen cycles suggest that their presence stimulates ecosystem metabolism. Phytoplankton communities were more dominated by cyanobacteria in lakes with hippos, and bacteria, zooplankton, and benthic invertebrate communities were similar regardless of hippo presence. Our results suggest that hippos recapitulate their role as ecosystem engineers in Colombia, importing terrestrial organic matter and nutrients with detectable impacts on ecosystem metabolism and community structure in the early stages of invasion. Ongoing range expansion may pose a threat to water resources.